Molar Pregnancy in Adolescents - Braga, Antonio; Growdon, Whitfield B.; Bernstein, Marilyn; Maestá, Izildinha [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Goldstein, Donald P.; Berkowitz, Ross S. (Sci Printers & Publ Inc, 2012)
OBJECTIVE: To describe the clinical presentation of hydatidiform molar pregnancy in women under the age of 20 years. In addition, we sought to understand if this adolescent population manifests differences in clinical factors compared to an adult population that may affect outcome.STUDY DESIGN: We used a database from the New England Trophoblastic Disease Center to analyze clinical data from all women followed for molar pregnancy between 1970 and 2009 with complete follow-up information. This population was stratified by age and clinical parameters including presenting signs, molar histology and development of gestational trophoblastic neoplasia (GTN). Univariable and multivariable logistic regression was employed to discern clinical factors that associated with adolescent age. The Partners Human Research Committee approved this study.RESULTS: We identified 1,494 women diagnosed with hydatidiform mole (HM), of which 220 (14.7%) were adolescents defined as age <20 years. The most common presenting clinical signs were vaginal bleeding and an enlarged uterus compared to dates. Median gestational age at diagnosis was 13.4 weeks, not different from that in the adult population. Similarly, no difference in presenting human chorionic gonadotropin was observed between the adult and adolescent populations. Adolescents presented with a significant overrepresentation of complete mole (86% vs. 75%, p < 0.001) compared to adults. Complete mole was associated with a heightened risk of developing GTN (OR 2.6, 95% CI 1.9-3.5), and despite the association of complete mole with young maternal age, univariable analysis showed no difference in the rate of GTN observed between adolescents and adults (24% vs. 30%, p = 0.08). Multivariable analysis controlling for molar histology demonstrated that adolescent age was associated with a decreased risk of GTN (hazard ratio 0.67, 95% CI 0.48 0.93).CONCLUSION: Adolescents account for a substantial proportion of the population with HM. They commonly present with vaginal bleeding. Though this population develops a complete mole with a higher frequency than adults, adolescents appear to have a significantly decreased risk of developing GTN. (J Reprod Med 2012; 57:225-230)
Keywords: adolescent pregnancy; adolescents; gestational trophoblastic neoplasia; hydatidiform mole; molar pregnancy